Clinical validation of Xpert MTB/RIF for the diagnosis of extrapulmonary tuberculosis - Tortoli, Enrico; Russo, Cristina; Piersimoni, Claudio; Mazzola, Ester; Dal Monte, Paola; Pascarella, Michela; Borroni, Emanuele; Mondo, Alessandra; Piana, Federica; Scarparo, Claudio; Coltella, Luana; Lombardi, Giulia; et al. (The European respiratory journal, 2012)
Extrapulmonary tuberculosis (EPTB) accounts for more than 20% of tuberculosis (TB) cases. Xpert MTB/RIF (Xpert) (Cepheid, Sunnyvale, CA, USA) is a fully automated amplification system, for which excellent results in the diagnosis of pulmonary TB in highly endemic countries have been recently reported. We aimed to assess the performance of the Xpert system in diagnosing EPTB in a low incidence setting. We investigated with Xpert a large number of consecutive extrapulmonary clinical specimens (1,476, corresponding to 1,068 patients) including both paediatric (494) and adult samples. We found, in comparison with a reference standard consisting of combination of culture and clinical diagnosis of TB, an overall sensitivity and specificity of 81.3% and 99.8% for Xpert, while the sensitivity of microscopy was 48%. For biopsies, urines, pus and cerebrospinal fluids the sensitivity exceeded 85%, while it was slightly under 80% for gastric aspirates. It was, in contrast, lower than 50% for cavitary fluids. High sensitivity and specificity (86.9% and 99.7%, respectively) were also obtained for paediatric specimens. Although the role of culture remains central in the microbiological diagnosis of EPTB, the sensitivity of Xpert in rapidly diagnosing the disease makes it a much better choice compared to smear microscopy. The ability to rule out the disease still remains suboptimal.